2020
DOI: 10.3390/biomedicines8070219
|View full text |Cite
|
Sign up to set email alerts
|

Thykamine Extracts from Spinach Reduce Acute Inflammation In Vivo and Downregulate Phlogogenic Functions of Human Blood Neutrophils In Vitro

Abstract: The anti-inflammatory and antioxidant role of Thykamine, a botanical extract of thylakoides obtained from spinach leaves, has been investigated in animal and cellular models. The oxidative properties have been proven by inhibiting NO production (>98%) in J774A.1 cells and by protecting a linoelic acid emulsion subjected to lipid peroxidation caused by AAPH. Thykamine injected intraperitoneally to rats reduced the inflammatory process of (TNBS)-induced colitis and carrageenan-induced paw edema. As neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this study, compared with the CK group, H group significantly increased WBC and GRAN, while M group and L group had no significant effect on blood routine indexes. The increase of these two indexes reflected the possibility of inflammation in the body [ 22 ]. Further determination of serum biochemical indicators, liver is the body’s detoxification organ, through the determination that serum ALT and AST activities can reflect the status of the liver [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, compared with the CK group, H group significantly increased WBC and GRAN, while M group and L group had no significant effect on blood routine indexes. The increase of these two indexes reflected the possibility of inflammation in the body [ 22 ]. Further determination of serum biochemical indicators, liver is the body’s detoxification organ, through the determination that serum ALT and AST activities can reflect the status of the liver [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial control in turn reduces the inflammatory response, which in turn decreases the plasma leakage in saliva through gingival crevicular fluid; this statement could be supported by the overall reduction in total salivary protein levels. (16) Further investigations: Several studies have reported anti-inflammatory effects of cocoa flavonoids,(36) thyme, (37) Artemisia annua, (38) Inonotus obliquus (chaga mushroom), (39) leaf extract of Ananas comosus, (40) Thykamine extracts from spinach (41) and White Willow Bark (Salix alba) (42) on different parts of the body. An analysis…”
Section: Antibacterial Effectsmentioning
confidence: 99%